2005
DOI: 10.1021/jf0509963
|View full text |Cite
|
Sign up to set email alerts
|

UV Treatment of Fishmeal:  A Method To Remove Dioxins?

Abstract: This study evaluates the use of UV on contaminated fishmeal and photodegradation of dioxins. Fishmeal samples were placed under UVA or UVB light for 2, 5, and 10 days. Subsequently, analysis of amino acid content, lipid oxidation marker, ethoxyquin content, dioxin, and polychlorinated biphenyl (PCB) profiling was carried out. Exposure of fishmeal for 5 days to UVB light resulted in the degradation of approximately 70% of the dioxin content, while UVA had little effect, only resulting in the degradation of 10% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Only limited effect was observed on improved fat separation after protease treatment of the fishmeal (30%) and on polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofuran (PCDD/F) and DL-PCB degradation by oxidoreductases (10-15%) (30). Exposure of fishmeal to UVB light has been shown to reduce the PCDD/F content by 70% (31). However, the photodegradation mechanism is probably coupled to lipid oxidation with non-and mono-ortho PCBs as reaction products (31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only limited effect was observed on improved fat separation after protease treatment of the fishmeal (30%) and on polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofuran (PCDD/F) and DL-PCB degradation by oxidoreductases (10-15%) (30). Exposure of fishmeal to UVB light has been shown to reduce the PCDD/F content by 70% (31). However, the photodegradation mechanism is probably coupled to lipid oxidation with non-and mono-ortho PCBs as reaction products (31).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of fishmeal to UVB light has been shown to reduce the PCDD/F content by 70% (31). However, the photodegradation mechanism is probably coupled to lipid oxidation with non-and mono-ortho PCBs as reaction products (31). The industrial use of the principle is questionable due to the need for a long exposure time (5 days) and increased lipid oxidation and DL-PCB content in the fishmeal after the UV treatment.…”
Section: Introductionmentioning
confidence: 99%
“…They have revealed an increase in the toxic equivalency concentration induced by the dechlorination of PCBs with 5 – 7 chlorine atoms. The concentrations of PCBs (#105, #118, #123, #158, #157, #167, and #189) with more chlorines and lower toxic equivalency factor (TEF) values decreased, while the concentration of PCBs (#77, #81, #126, and #169) with less chlorine and higher TEF value increased after 5 days of UV irradiation [60] . In this study, no dioxin-like PCBs were detected in the photolytic process using Aroclor 1260.…”
Section: Resultsmentioning
confidence: 99%
“…The latter technology will also remove most of the fat content in the fishmeal and give a product with altered chemical composition and physical properties. Other relevant or targeted studies reported in the literature include improved fat separation, organic solvent extraction, degradation by oxidoreductases, and UV treatment . However, these technologies have either limited effect or are not or difficult to implement in industrial‐scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Other relevant or targeted studies reported in the literature include improved fat separation, 9,22 -25 organic solvent extraction, 24 degradation by oxidoreductases, 24 and UV treatment. 26 However, these technologies have either limited effect or are not or difficult to implement in industrial-scale production.…”
Section: Introductionmentioning
confidence: 99%